Teaching your children healthy sexuality : a biblical approach to prepare them for life - Burns, Jim, 1953- (Minneapolis, Minn. : Bethany House, 2008)
"Experienced family authority Jim Burns provides a simple and practical guide for parents to help their children develop a healthy and biblical perspective regarding their bodies and sexuality"--Provided by publisher.
Teaching your kids value-centered sexuality -- Building a foundation to teach the Purity Code -- Helping your kids set standards -- How and when to talk with your kids about sex and sexuality -- Sex outside of maarriage: choices and consequences -- Sexual abuse : prevention and help -- Dealing with your own sexuality -- Questions and answers -- Discussion starters and faith conversations.
Includes bibliographical references (p. 151-154).
Keywords: Sex -- Religious aspects -- Christianity; Sex instruction for children